Yemen’s Democracy Experiment in Regional Perspective - Phillips, S. author. aut Link
VII, 241 p.
Keywords: This study examines the nature of changes to Yemen's power structures, political dynamics and institutions since the intention to democratize was announced in 1990 paying particular attention to the role of Yemeni President Ali Abdullah Saleh.